1998
DOI: 10.1021/ja980606b
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Geometric Variations in Perturbed Blue Copper Centers:  Electronic Structures of Stellacyanin and Cucumber Basic Protein

Abstract: The electronic structures of the perturbed blue copper proteins stellacyanin (STC) and cucumber basic protein (CBP, also called plantacyanin, PNC) are defined relative to that of the well-understood “classic” site found in plastocyanin (PLC) by combining the results of low-temperature optical absorption, circular dichroism, and magnetic circular dichroism spectra with density functional calculations. Additionally, absorption and magnetic circular dichroism spectra of Alcaligenes denitrificans wild-type and M12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
244
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(263 citation statements)
references
References 37 publications
18
244
1
Order By: Relevance
“…[5][6][7] Closely related blue copper sites, such as cucumber basic protein, pseudoazurin and nitrite reductase, each have a slightly distorted active site compared to plastocyanin and exhibit remarkably different spectral features, in particular an increased intensity of the higher energy band. 4,8 Furthermore, recent studies have shown that a closely related protein, nitrosocyanin, adsorbs in the red. 9 This results from a change in the nature of the intense transition from an excitation from a cysteine-Cu p-like orbital to a s -like one.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Closely related blue copper sites, such as cucumber basic protein, pseudoazurin and nitrite reductase, each have a slightly distorted active site compared to plastocyanin and exhibit remarkably different spectral features, in particular an increased intensity of the higher energy band. 4,8 Furthermore, recent studies have shown that a closely related protein, nitrosocyanin, adsorbs in the red. 9 This results from a change in the nature of the intense transition from an excitation from a cysteine-Cu p-like orbital to a s -like one.…”
Section: Introductionmentioning
confidence: 99%
“…The long thioether bond reduces its donor interaction with the copper which is compensated by the thiolate leading to the short Cu-S(Cys) bond of 2.1 Å in the blue copper sites. This long thioether/short thiolate would eliminate all orbital degeneracy of the oxidized site; thus, there would be no Jahn-Teller distortion from the tetrahedral to a tetragonal structure.The above ''coupled distortion'' model provided an explanation for a series of blue copper related proteins (i.e., same Cys, Met, 2His ligand set) which changed from blue to green in color in going from plastocyanin to nitrite reductase (NiR) (5,22,23). In the latter protein the Cu-S(Met) bond has decreased to 2.45 Å, the Cu-S(Cys) bond has elongated to 2.21 Å, and the S-Cu-S plane has rotated relative to the N-Cu-N plane to a more tetragonal structure (24).…”
mentioning
confidence: 99%
“…This leads to a small geometry change on reduction from Cu(II) to Cu(I), 3,4 resulting in a small reorganization energy and high rate of electron transfer. 5 The oxidised forms of blue copper proteins have a d 9 electronic configuration that results in distinctive absorption spectra, [6][7][8][9] with an intense band at about 2.1 eV (16 700 cm 1 ). This band is often referred to as arising from a ligand to metal charge transfer (LMCT) transition, which corresponds to an excitation from the Cys p orbital to the singly occupied orbital (SOMO).…”
Section: Introductionmentioning
confidence: 99%
“…10 Blue copper proteins have also been studied with electronic circular dichroism (CD) spec-troscopy. 6,7 There are more distinct bands in the CD spectra compared to the absorption spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation